Lignin nanoparticles in food packaging: a sustainable approach to material design and performance enhancement - Peng, Jinqian; Wang, Yu (Frontiers in Nutrition, 2025)
The global food packaging industry is undergoing a transformative shift toward sustainable alternatives to conventional petroleum-based materials, driven by escalating environmental concerns, regulatory pressures, and consumer demand for greener products. Biodegradable polymers such as chitosan, starch, cellulose, PLA, and PBS have gained prominence due to their renewability and reduced ecological footprint. However, their inherent limitations, including poor mechanical strength, moisture sensitivity, and limited bioactivity, have restricted widespread adoption. Lignin nanoparticles (LNPs), derived from the abundant and underutilized biopolymer lignin, have emerged as multifunctional nanofillers capable of significantly enhancing the structural and functional properties of biodegradable films. Owing to their antioxidant, UV-blocking, antimicrobial, and barrier-enhancing characteristics, LNPs improve film performance while aligning with circular economy principles. This review critically examines the sources, structural characteristics, extraction methods, and synthesis techniques of lignin, emphasizing their impact on nanoparticle formation and functionality. It further explores recent advances in LNP-reinforced packaging systems across diverse biopolymer matrices, including polysaccharides, proteins, and biodegradable polyesters. Special attention is given to interfacial interactions, dispersion behavior, and structure–property correlations. Finally, emerging trends such as LNP surface engineering, smart coating systems, and hybrid fabrication strategies are discussed in the context of future scalability, recyclability, and regulatory compliance.